Edukasi Pada Ibu Menyusui Tentang Pemberian Kombinasi Hypnobreastfeeding dan Aromaterapi Rose Terhadap Produksi ASI di Kota Padang - Zilfi Yola Pitri; Kholilah Lubis (Jurnal Pengabdian Masyarakat, 2026)
Exclusive breastfeeding is crucial in supporting the growth and development of infants, such as increasing antibodies, protecting against infectious diseases, and several other benefits. Education on Hypnobreastfeeding, a method for increasing breast milk that is beneficial for breastfeeding mothers in Padang City has physical and psychological benefits for the mother. This community service aims to increase the knowledge of pregnant women about the benefits of breast milk. The type of activity carried out is in the form of health education related to the benefits of Hypnobreastfeeding for smooth breast milk flow. The instrument used to measure the level of knowledge of breastfeeding mothers is a questionnaire with 10 structured questions about breast milk, the measurement results of this questionnaire are the level of knowledge of good, sufficient and less. This activity was preceded by a pre-test to measure the level of knowledge of pregnant women before receiving the counseling material and followed by a post-test to measure the level of knowledge of pregnant women after receiving the counseling material. The number of counseling participants was 29 people, after the counseling, several results were obtained, namely there was an increase in the percentage of the good knowledge group by 65%, the sufficient knowledge group by 35%, and no participants were found with a low level of knowledge.